2022
DOI: 10.1002/dmrr.3551
|View full text |Cite
|
Sign up to set email alerts
|

Associations of maternal gestational diabetes mellitus with alterations in cardiovascular system in early childhood

Abstract: Aims:The association of maternal gestational diabetes mellitus (GDM) with childhood cardiovascular alterations is not well established. This study aims to test the hypothesis that prenatal exposure to GDM is associated with vascular and cardiac alterations in early childhood. Methods:In a population-based prospective cohort among 1094 mothers and their offspring, GDM was diagnosed according to the International Association of Diabetes and Pregnancy Study Groups criteria. Childhood blood pressure (BP) measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…ADA diabetes classification criteria were used in six studies for PDM and GDM ( 5 , 28 , 35 , 37 , 38 , 43 ), NICE criteria were used in one study for GDM ( 25 ), and WHO criteria were used in three studies for GDM ( 2 , 23 , 42 ). Four studies used local diagnostic criteria for PDM and GDM ( 3 , 32 , 34 , 40 ), and 17 studies did not address criteria for diabetes diagnosis at all.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ADA diabetes classification criteria were used in six studies for PDM and GDM ( 5 , 28 , 35 , 37 , 38 , 43 ), NICE criteria were used in one study for GDM ( 25 ), and WHO criteria were used in three studies for GDM ( 2 , 23 , 42 ). Four studies used local diagnostic criteria for PDM and GDM ( 3 , 32 , 34 , 40 ), and 17 studies did not address criteria for diabetes diagnosis at all.…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen studies reported maternal HbA1c and/or diabetes therapy. Analysis of echocardiography was blinded in 12 studies ( 1 , 4 , 6 , 7 , 25 , 28 , 31 , 37 , 38 , 41 , 43 , 44 ). Five studies adjusted for potential confounders such as race, birth weight, maternal age and time elapsed from delivery to postnatal outcome acquisition ( 3 , 25 , 41 , 43 , 44 ).…”
Section: Resultsmentioning
confidence: 99%
“…A study reported that maternal hyperglycemia during the first half of pregnancy was associated with lower childhood left ventricular mass and left ventricular end-diastolic volume [5]. Offspring of mothers with gestational diabetes mellitus (GDM) exhibited higher blood pressure and cardiac structural changes during early childhood [19,20]. Kaseva et al assessed cardiometabolic biomarkers and blood pressure in adult offspring of mothers with GDM and found increased markers of insulin resistance and a more atherogenic lipid profile [21].…”
Section: Maternal Diabetesmentioning
confidence: 99%
“…Regardless of GDM diagnosis, maternal hyperglycemia along the whole spectrum has been linearly associated with adverse perinatal outcomes in both mother and offspring [ 5 ]. Exposure to maternal hyperglycemia in utero is also associated with an increased risk for the development of chronic diseases later in childhood, including obesity [ 6 ], metabolic [ 7 ] and cardiovascular diseases [ 8 ], asthma [ 9 ], autism [ 10 ], as well as other adverse neurodevelopmental outcomes [ 11 ]. The Developmental Origin of Health and Disease (DOHaD) hypothesis is central to the concept of fetal programming and based on lasting fetal metabolic adaptions to environmental/maternal stressors during the critical developmental period [ 12 ].…”
Section: Introductionmentioning
confidence: 99%